Brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine in patients with advanced‐stage, classical Hodgkin lymphoma: A prespecified subgroup analysis of high‐risk patients from the ECHELON‐1 study. Issue 2 (16th February 2021) - Hutchings, Martin; Radford, John; Ansell, Stephen M.; Illés, Árpád; Sureda, Anna; Connors, Joseph M.; Sýkorová, Alice; Shibayama, Hirohiko; Abramson, Jeremy S.; Chua, Neil S.; Friedberg, Jonathan W.; Kořen, Jan; et al.
Abstract: Approximately one‐third of patients diagnosed with Hodgkin lymphoma presenting with Stage IV disease do not survive past 5 years. We present updated efficacy and safety analyses in high‐risk patient subgroups, defined by Stage IV disease or International Prognostic Score (IPS) of 4–7, enrolled in the ECHELON‐1 study that compared brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine (A + AVD) versus doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) as first‐line therapy after a median follow‐up of 37.1 months. Among patients treated with A + AVD ( n  = 664) or ABVD ( n  = 670), 64% had Stage IV disease and 26% had an IPS of 4–7. Patients with Stage IV disease treated with A + AVD showed consistent improvements in PFS at 3 years as assessed by investigator (hazard ratio [HR], 0.723; 95% confidence interval [CI], 0.537–0.973; p =  0.032). Similar improvements were seen in the subgroup of patients with IPS of 4–7 (HR, 0.588; 95% CI, 0.386–0.894; p  = 0.012). The most common adverse events (AEs) in A + AVD‐treated versus ABVD‐treated patients with Stage IV disease were peripheral neuropathy (67% vs. 40%) and neutropenia (71% vs. 55%); in patients with IPS of 4–7, the most common AEs were peripheral neuropathy (69% vs. 45%), neutropenia (66% vs. 55%), and febrile neutropenia (23% vs. 9%), respectively. Patients in high‐risk subgroups did not experience greater AE incidence or severity than patients in the total population. This updated analysis of ECHELON‐1 shows a favorable benefit‐risk balance in high‐risk patients.